Biological variation of β-sitosterol, campesterol, and lathosterol as cholesterol absorption and synthesis biomarkers - Wu, Alan H.B.; Ruan, Weiming; Todd, John; Lynch, Kara L. (Clinica chimica acta, 2014)
The analysis of blood for β-sitosterol and campesterol is the measures of cholesterol absorption while lathosterol is a measure of cholesterol synthesis. The biological variability of β-sitosterol, campesterol, and lathosterol was measured using liquid-chromatography tandem mass spectrometry from a cohort of 25 apparently healthy subjects, where blood was taken once every weeks for 6weeks. The analytical, intra-individual, and group inter-individual variations (CVA, CVI, and CVG, respectively) were calculated. Using absolute values, the CVI for β-sitosterol, campesterol, and lathosterol was 11.8%, 11.8%, and 22.5%, respectively, and the CVG was 28.5%, 28.8%, and 52.0%, respectively. This produced reference change values of about 24–36% for declining values and 32–47% for increasing values. The index of individuality was between 0.41 and 0.58, indicating that population based reference values are of little use for these biomarkers. The number of points needed for a homeostatic setpoint was 5 samples for β-sitosterol and campesterol, and 19 samples for lathosterol. Similar findings were observed for values when normalized to total cholesterol. These results were higher than the biological variation for total, low density and high density cholesterol obtained from the literature. Results were essentially identical when sterol values were corrected to their respective total cholesterol concentration. The establishment of the biological variation for these biomarkers enables their use in the interpretation of results from clinical trials and lipid lowering treatment of patients at risk for cardiovascular disease in clinical practice. •Statins are used to treat patients who over-produce cholesterol.•Ezetimibe is used to treat patients who over-absorb cholesterol.•Lathosterol is a biomarker for cholesterol synthesis.•Campesterol and β-sitosterol are biomarkers for cholesterol absorption.•The biological variation of these markers was measured from healthy donors.